Seismic Response Analysis of Buckling-Restrained Brace Frames Considering Brace Performance Degradation - Ma, Qianying; Li, Yu; Xiong, Kun; Meng, Chenyang; Zhou, Jiale (Civil Engineering Journal, 2025)
To elucidate the degradation mechanisms of the hysteretic behavior of buckling-restrained braces (BRBs) in hot–humid service environments and their implications for structural seismic performance, this study tested six BRBs of identical specifications under different numbers of hygrothermal cycles (0, 24, 48, 72, 96, and 120), combining alternating high–low temperature hygrothermal exposure with subsequent quasi-static cyclic loading. The evolution of hysteretic performance parameters with cycle count was quantified. Test results indicate that hygrothermal cycling induces corrosion of the steel core and deterioration of the unbonded material, weakening interfacial bond strength and increasing axial friction effects; consequently, the tensile yield load, elastic stiffness, and ultimate tensile capacity decrease. Based on the experimental observations, a modified Bouc–Wen model was employed to simulate BRB hysteretic nonlinearity, and the identified parameter evolution closely reproduced the measured trends. The degradation model was further incorporated into time-history analyses to assess the influence of BRB performance deterioration on structural response for four representative bracing layouts: single-diagonal (symmetric), single-diagonal (asymmetric), chevron (inverted-V), and multi-story X-braced schemes. All layouts significantly reduced seismic responses; among them, the chevron configuration exhibited the lowest sensitivity to degradation, with response amplification after 120 hygrothermal cycles markedly lower than that of the single-diagonal asymmetric scheme. The findings provide an experimental basis and design reference for seismic design and durability assessment of structures in long-term hot–humid service regions.